Goal-Directed Behavior. - Aarts, Henk (Frontiers of social psychology., 2012)
This volume presents chapters from internationally renowned scholars in the area of goals and social behavior. The book is organized around a series of topics that are of critical importance to understanding the social-cognitive aspects of goal-directed behavior. In each chapter, the authors offer an introduction to past research on a specific topic and combine this with a presentation of their own empirical work to provide an integrated overview of the topic at hand. As a whole, this volume is designed to provide a broad portrait of goal research as it has been and is currently being condu.